1976
DOI: 10.1111/j.1432-1033.1976.tb10840.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forms of Electrophorus Acetylcholinesterase

Abstract: Molecular weights for the series of six Electrophorus acetylcholinesterase forms have been determined either by the sedimentation‐diffusion equilibrium method or, particularly in the case of the very scarce G′ and G″ forms, from their Stokes radius and sedimentation coefficient values. Both methods are in excellent agreement. The results provide good evidence for the model previously proposed, G″, G′ and G containing one, two and four subunits, whereas A, C and D possess, in addition to respectively one, two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

1976
1976
1985
1985

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 22 publications
5
26
1
Order By: Relevance
“…Electron micrographs [5,6] have shown that the asymmetric forms contain a rod-like structure, the 'tail'. We have deduced the number of catalytic subunits from molecular weight data for all forms [7], confirming a model previously proposed [5,6] according to which A, C, D are composed, in addition to a rod like 'tail', of one, two and three tetramers respectively. The forms G, G' and G" are tetramers, dimers and monomers.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Electron micrographs [5,6] have shown that the asymmetric forms contain a rod-like structure, the 'tail'. We have deduced the number of catalytic subunits from molecular weight data for all forms [7], confirming a model previously proposed [5,6] according to which A, C, D are composed, in addition to a rod like 'tail', of one, two and three tetramers respectively. The forms G, G' and G" are tetramers, dimers and monomers.…”
Section: Introductionsupporting
confidence: 48%
“…No specific band, either proteic or glycoproteic, could be assigned to the tail of the asymmetric forms. Electron microscopy [6] and molecular weight data [7] have indicated that the tail may consist of three 30 000 dalton chains. When the asymmetric forms were analyzed without reduction, no 30 000 dalton band was visible: it may be that the three tail chains were linked together by disulfide bridges and cofncided in the gel with the monomeric band or, alternately, that they were linked to the catalytic subunits via disulfide bridges.…”
Section: Intra-and Inter-subunit Disulfide Bondsmentioning
confidence: 99%
“…It should be noted that these methods do not permit the calculation of the protein frictional ratio from the M r and the sedimentation coefficient of the protein-detergent complex. Thus, it is not possible to decide whether dimeric human erythrocyte membrane acetylcholinesterase is an asymmetric or a globular enzyme form [13].…”
Section: Discussionmentioning
confidence: 99%
“…Stokes' radii were determined by molecular sieve chromatography (Biogel A 15 m) for A, C and D forms, as described in [5] and [9]. In the case of the aggregates, a Biogel A 50 m column was used (height 90 cm, diameter 1.5 cm).…”
Section: Hydrodynamic Characteristicsmentioning
confidence: 99%